2017
DOI: 10.1055/s-0037-1604399
|View full text |Cite
|
Sign up to set email alerts
|

The Global Initiative for Children's Surgery: Optimal Resources for Improving Care

Abstract: The Optimal Resources document has been produced by surgical providers from LMICs who have the greatest insight into the needs and priorities in their population. The document will be refined further through online GICS Working Groups and the World Health Organization for broad application to ensure all children have timely access to safe surgical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 14 publications
2
65
0
1
Order By: Relevance
“…However, there is very limited population-based data from LMICs including Nigeria, and most of the policies have been based on extrapolations from hospital-based studies which are fraught with many inaccuracies. Furthermore, most National Surgical Health Plans have so far not addressed children's surgery [15]. This study provides much-needed data on the burden of paediatric surgical diseases for policy makers in our country.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is very limited population-based data from LMICs including Nigeria, and most of the policies have been based on extrapolations from hospital-based studies which are fraught with many inaccuracies. Furthermore, most National Surgical Health Plans have so far not addressed children's surgery [15]. This study provides much-needed data on the burden of paediatric surgical diseases for policy makers in our country.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO, this proportion could increase to more than 45% by 2030 [3]. The impact appears to be greater for the paediatric population of low-and middle-income countries [6]. In a recent survey, an unmet need for paediatric surgical care was estimated in 62% of children in lowincome countries [7].…”
Section: Discussionmentioning
confidence: 99%
“…In liver transplantation, these technologies have rapidly expanded with multiple devices and systems routinely being used clinically. Normothermic machine perfusion (NMP) has proven to be an exciting technology, with international multicentre randomized control trial data demonstrating its ability to reduce graft injury, prolong preservation and increase utilisation [13,14]. Further studies have reported on sequential SCS and NMP with comparable clinical outcomes to continuous NMP alone, providing robust clinical data in support of the more logistically straightforward 'back to base model' of liver NMP [15].…”
Section: Normothermic Machine Perfusion Of the Livermentioning
confidence: 99%